Translanguaging Practices in a Hungarian-English Early Childhood Classroom - (:unkn) unknown (IGI Global, 2020)
After a brief overview of translanguaging research carried out in the past, this chapter introduces how Hungarian-English emergent bilingual children used translanguaging practices during play time in a Hungarian-English early childhood education classroom in the AraNY János Hungarian School in New York City (USA). The authors developed the concept of student-led translanguaging and observed it separately from teacher-led translanguaging practices. This chapter presents the data collected through classroom observations over a period of 6 months. The overarching aim of this research is to reveal how translanguaging is used by the students and by the teachers in a superdiverse community of Hungarian descendants living around New York City.